2019
DOI: 10.1038/s41467-019-12448-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inter-species conjugative transfer of a CRISPR nuclease for targeted bacterial killing

Abstract: The selective regulation of bacteria in complex microbial populations is key to controlling pathogenic bacteria. CRISPR nucleases can be programmed to kill bacteria, but require an efficient and broad-host range delivery system to be effective. Here, using an Escherichia coli and Salmonella enterica co-culture system, we show that plasmids based on the IncP RK2 conjugative system can be used as delivery vectors for a TevSpCas9 dual nuclease. Notably, a cis-acting plasmid that encodes the conjugation and CRISPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 51 publications
1
118
0
Order By: Relevance
“…Among these, CRISPR (clustered regularly interspaced short palindromic repeats)-Cas3and Cas9-encoding phages provide a means to combat such threats by selectively killing AMR bacteria 6 . The CRISPR-Cas3 and CRISPR-Cas9 genome-editing constructs, which were designed to target AMR genes, were delivered into bacteria by packaging them into phages [7][8][9][10][11] to achieve AMR gene-specific bacterial killing [7][8][9][10][11][12] and prevent the spread of AMR genes 7 . However, because DNA cleavage of plasmid DNA does not result in bacterial death, at least not in the absence of other confounding variables, such as a toxin-antitoxin system, this strategy is ineffective in targeting bacteria with plasmid-borne AMR genes 9 .…”
mentioning
confidence: 99%
“…Among these, CRISPR (clustered regularly interspaced short palindromic repeats)-Cas3and Cas9-encoding phages provide a means to combat such threats by selectively killing AMR bacteria 6 . The CRISPR-Cas3 and CRISPR-Cas9 genome-editing constructs, which were designed to target AMR genes, were delivered into bacteria by packaging them into phages [7][8][9][10][11] to achieve AMR gene-specific bacterial killing [7][8][9][10][11][12] and prevent the spread of AMR genes 7 . However, because DNA cleavage of plasmid DNA does not result in bacterial death, at least not in the absence of other confounding variables, such as a toxin-antitoxin system, this strategy is ineffective in targeting bacteria with plasmid-borne AMR genes 9 .…”
mentioning
confidence: 99%
“…2). It is widely observed that Cas9 and its mutant dCas9 may exhibit off-target activity and/or sequence-specific toxicity in target organisms such as E. coli (Cui et al 2018;Hamilton et al 2019) and clostridia (Xu et al 2015). Previously, we observed cloning difficulties with plasmid piCas in E. coli DH5α which could be overcome by cloning of Lac repressor operator sequence (lacO) at the transcriptional starting site of the employed m2p promoter (Schultenkämper et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…102 Conjugative plasmids that encode and promote biofilm formation could increase rates of conjugative plasmid transfer due to the enhanced cell-to-cell contact, 103 which may be suited for delivery of molecular tools such as CRISPR nucleases for modulating composition of microbial communities 104,106 that many of them exist as biofilms. In a study by Hamilton et al, 107 they developed a cis-conjugative system that the plasmid encodes both CRISPR nuclease and conjugative machinery. They designed 65 total sgRNA, which target 38, 23, and 4 essential genes, non-essential genes and genes with unresolved phenotypes.…”
Section: Crispr-cas System Neutralizing Antibiotic-resistant Genesmentioning
confidence: 99%